2000
DOI: 10.1063/1.126510
|View full text |Cite
|
Sign up to set email alerts
|

Metallization scheme for highly low-resistance, transparent, and thermally stable Ohmic contacts to p-GaN

Abstract: We report on a promising metallization scheme for high-quality Ohmic contacts to surface-treated p-GaN:Mg (2 -3ϫ10 17 cm Ϫ3 ). It is shown that the as-deposited Pt/Ru contact produces a specific contact resistance of 7.8(Ϯ2.2)ϫ10 Ϫ4 ⍀ cm 2 . However, annealing of the contact at 600°C for 2 min results in a resistance of 2.2(Ϯ2.0)ϫ10 Ϫ6 ⍀ cm 2 . It is also shown that the light transmittance of the annealed contact is 87.3% at 470 nm. Furthermore, the surface of the contact annealed at 600°C for 30 min is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Other approaches aim at lowering the Schottky barrier height (SBH) by chemical passivation and removal of oxide layer on p-GaN [12][13][14]. More recently, promising approaches using Ni-based alloys such as Ni-La, Ni-Zn, Ni-Mg, and Ni-Cu produced very low specific contact resistivity in 10 −5 ∼10 −6 cm 2 range, depending on metal schemes [15][16][17][18].…”
mentioning
confidence: 98%
“…Other approaches aim at lowering the Schottky barrier height (SBH) by chemical passivation and removal of oxide layer on p-GaN [12][13][14]. More recently, promising approaches using Ni-based alloys such as Ni-La, Ni-Zn, Ni-Mg, and Ni-Cu produced very low specific contact resistivity in 10 −5 ∼10 −6 cm 2 range, depending on metal schemes [15][16][17][18].…”
mentioning
confidence: 98%
“…In fact, the high contact resistance of GaN is one of major obstacles to the realisation of long-lifetime operation of GaN-based optical devices. Thus, to develop high-quality Ohmic contacts, different surface treatments using KOH [2], HNO 3 : HCl [3], buffered oxide etch (BOE) [4,5], (NH 4 ) 2 S x [6], and Na 2 S [7] solutions have been employed. Kim et al [3] showed that for Pd/Au Ohmic contacts to p-GaN, the surface treatment with HNO 3 : HCl leads to a specific contact resistance of $10 --4 W cm 2 .…”
mentioning
confidence: 99%
“…The low resistance was attributed to the effective removal of native oxide. Jang et al [4,5] showed that the two-step surface treatment with BOE is an effective process for the removal of native oxide and causes an increase in the carrier concentration at the surface region, resulting in a large reduction in the specific contact resistance. Huh et al [6] showed that the surface modification with alcohol-based (NH 4 ) 2 S x solutions is effective in improving the Ohmic contact behaviour.…”
mentioning
confidence: 99%
“…However, because of difficulty in obtaining a hole concentration over 10 18 cm --3 and the absence of metals having a work function higher than that of p-GaN, achieving low resistance ohmic contacts to p-GaN has been particularly challenging. So far, many experiments on the electrical characteristics of metal contacts to p-GaN have been carried out, mainly focusing on the variation of metal scheme and surface treatments [2][3][4]. In order to achieve the low-resistance ohmic contacts to p-GaN, understanding of the carrier transport phenomena at the interface between metal and p-GaN is essential.…”
mentioning
confidence: 99%